A Central Metabolic Circuit Controlled by QseC in Pathogenic Escherichia coli - Hadjifrangiskou, Maria (2011)
The QseC sensor kinase regulates virulence in multiple gram-negative pathogens, by controlling the activity of the QseB response regulator. We have previously shown that qseC deletion interferes with dephosphorylation of QseB thus unleashing what appears to be an uncontrolled positive feedback loop stimulating increased QseB levels. Deletion of QseC downregulates virulence gene expression and attenuates enterohemorrhagic and uropathogenic Escherichia coli (EHEC and UPEC), Salmonella typhimurium, and Francisella tularensis. Given that these pathogens employ different infection strategies and virulence factors, we used genome-wide approaches to better understand the role of the QseBC interplay in pathogenesis. We found that deletion of qseC results in misregulation of nucleotide, amino acid, and carbon metabolism. Comparable metabolic changes are seen in EHEC ΔqseC, suggesting that deletion of qseC confers similar pleiotropic effects in these two different pathogens. Disruption of representative metabolic enzymes phenocopied UPEC ΔqseC in vivo and resulted in virulence factor downregulation. We thus propose that in the absence of QseC, the constitutively active QseB leads to pleiotropic effects, impairing bacterial metabolism, and thereby attenuating virulence. These findings provide a basis for the development of anti-microbials targeting the phosphatase activity of QseC, as a means to attenuate a wide range of QseC-bearing pathogens.